Chrudim's Christ and Miraculous Context of his Legend (Theatrum historiae, 2009)
The paper deals with the St. Salvator's painting kept in the Church of the Assumption of the Virgin Mary in Chrudim, which became worshipped as an antiplague Paladium of baroque Bohemia and Moravia during the pestilence epidemics in years 1680 and 1713–1715. Early Modern Ages created several opposite theories on its historical origin – the scholars looked for its provenance in the Biblical Era, within the artistic collections of the emperors and Bohemian kings Charles IV. and Rudolf II., or they made a groundless direct connection between the oil-painting and the works of German Renaissance painter Lucas Cranach the Elder. But this late mannerist oil-on-wood influenced by Dutch naturalism and representing an impressive replica of Vera Effigies won ́t be coming from an earlier period than the turn of the16th and the17th Centuries. The picture came to Chrudim a bit later and in 1648 it played a lead role in the brutal vituparation acted by Swedish Lutherans. The result of this physical iconoclastic disgrace made on the artwork was an ineffaceable bloody hack on the temple of St. Salvator and some other transformations of his face. This moment in the history of the painting has stimulated a strong private piety which has been consequently changed to the strong public worship during the last quarter of the 17th Century. The main promoter of Chrudim's St. Salvator cult was the dean Samuel Hataš (†1685) and later it was excited by the baroque book Nebeský Lékař Kristus Ježíš (Celestial Healer Jesus Christ) by Václav Baltazar Petržilka, printed in Czech language (1718 and 1735) and later in German (1764). The proposed paper also deals with several other baroque sculptures and paintings, influnced by the picture of Chrudim's St. Salvator, which later officially propagated its miraculous legend.